Flexible and Wire-Shaped Micro-Supercapacitor Based on Ni(OH)2-Nanowire and Ordered Mesoporous Carbon Electrodes - Dong, Xiaoli; Guo, Ziyang; Song, Yanfang; Hou, Mengyan; Wang, Jianqiang; Wang, Yonggang; Xia, Yongyao (Advanced functional materials, 2014)
Portable and multifunctional electronic devices are developing in the trend of being small, flexible, roll‐up, and even wearable, which asks us to develop flexible and micro‐sized energy conversion/storage devices. Here, the high performance of a flexible, wire‐shaped, and solid‐state micro‐supercapacitor, which is prepared by twisting a Ni(OH)2‐nanowire fiber‐electrode and an ordered mesoporous carbon fiber‐electrode together with a polymer electrolyte, is demonstrated. This micro‐supercapacitor displays a high specific capacitance of 6.67 mF cm–1 (or 35.67 mF cm–2) and a high specific energy density of 0.01 mWh cm–2 (or 2.16 mWh cm–3), which are about 10–100 times higher than previous reports. Furthermore, its capacitance retention is 70% over 10 000 cycles, indicating perfect cyclic ability. Two wire‐shaped micro‐supercapacitors (0.6 mm in diameter, ≈3 cm in length) in series can successfully operate a red light‐emitting‐diode, indicating promising practical application. Furthermore, synchrotron radiation X‐ray computed microtomography technology is employed to investigate inner structure of the micro‐device, confirming its solid‐state characteristic. This micro‐supercapacitor may bring new design opportunities of device configuration for energy‐storage devices in the future wearable electronic area. The high performance of a flexible, wire‐shaped, and solid‐state micro‐supercapacitor, which is prepared by twisting a Ni(OH)2‐nanowire fiber‐electrode and an ordered mesoporous carbon fiber‐electrode together with solid‐state polymer electrolyte, is demonstrated.